2015
DOI: 10.1073/pnas.1420279112
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a groundwater supply contamination incident attributed to Marcellus Shale gas development

Abstract: High-volume hydraulic fracturing (HVHF) has revolutionized the oil and gas industry worldwide but has been accompanied by highly controversial incidents of reported water contamination. For example, groundwater contamination by stray natural gas and spillage of brine and other gas drilling-related fluids is known to occur. However, contamination of shallow potable aquifers by HVHF at depth has never been fully documented. We investigated a case where Marcellus Shale gas wells in Pennsylvania caused inundation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
241
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(254 citation statements)
references
References 21 publications
6
241
1
Order By: Relevance
“…In particular, a subset (n = 12) of groundwater liquid-liquid extracts was analyzed, including those with the highest DRO levels, along with a field blank and one natural salt spring in Susquehanna County, Pennsylvania, that is typically used to indicate the composition of natural gas and brine-rich fluids derived from shale rock sources in the northern Appalachian Basin (7)(8)(9)(10)(11)(12). The samples with the highest DRO (n = 2) contained bis(2-ethylhexyl) phthalate (Fig.…”
Section: −27mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a subset (n = 12) of groundwater liquid-liquid extracts was analyzed, including those with the highest DRO levels, along with a field blank and one natural salt spring in Susquehanna County, Pennsylvania, that is typically used to indicate the composition of natural gas and brine-rich fluids derived from shale rock sources in the northern Appalachian Basin (7)(8)(9)(10)(11)(12). The samples with the highest DRO (n = 2) contained bis(2-ethylhexyl) phthalate (Fig.…”
Section: −27mentioning
confidence: 99%
“…Although few studies have examined the occurrence and origin of organic contaminants in groundwater in HVHF regions (7), the presence of light hydrocarbon gases (i.e., methane and ethane) and inorganic constituents has been investigated frequently. Osborn et al (8) and Jackson et al (9) demonstrated elevated methane levels within 1 km of unconventional gas wells over the Marcellus Shale.…”
mentioning
confidence: 99%
“…Such technology mentioned above has played a very important role in the shale gas revolution. However, with the development of nature gas engineering, the defects of the fracturing technology with water-base fracturing fluids are exposed gradually, such as (1) water wasting, especially in the areas of water deficient, for example, the Chinese Ordos area, where the large-scale fracturing with water-base fluids is difficult to be implemented; (2) water lock effect and the Jamin effect, which will occur along with the water injection and result in blocking the gas migration channel and impairing the productivity [9,10]; and (3) fracturing fluid backflow problem, the fluids contain many chemical ingredients which will cause the unrecoverable damage to the stratum and the underground water pollution [11,12].…”
Section: State Of the Artmentioning
confidence: 99%
“…Research on this topic has proliferated exponentially over the last half decade; much research focuses on impacts associated with development (Sovacool 2014). Scientists have afforded particular attention to effects on the following: (1) water quality (Entrekin et al 2011, Jackson et al 2013, Olmstead et al 2013, Vidic et al 2013, Vengosh et al 2014, Llewellyn et al 2015, (2) air quality (Moore et al 2014), (3) global climate change (Alvarez et al 2012, Allen et al 2013, Newell and Raimi 2014, (4) biota/ecosystems (Drohan et al 2012, Kiviat 2013, Souther et al 2014, Milt et al 2015, (5) human health (New Brunswick Department of Health 2012, Kibble et al 2013, Adgate et al 2014, Kovats et al 2014 Institute for Applied Environmental Health 2014), (6) local and regional economics (Kinnaman 2011, Weber 2012, Fry et al 2015, and (7) community well-being (Jacquet 2014, Jacquet and Stedman 2014, Evensen 2015. These impacts could contribute to or challenge the prospects for sustainable and resilient futures in the communities where they are experienced.…”
Section: Introductionmentioning
confidence: 99%